Traços de personalidade, fenômeno do impostor e estilos parentais: Um estudo correlacional com crianças - Renata Tereza dos Passos Costa (2024)
Perceiving oneself as a fraud, doubting one's own ability, despite evident accomplishments are characteristics of people with imposter feelings. The impostor phenomenon has the potential to generate impacts on the individual's mental health and well-being, and therefore should be studied in depth, and can be related to several variables capable of elucidating this construct. In this way, personality traits and parenting styles are important for their understanding. To do this, a systematic review of the literature was carried out with the objective of verifying the relationships between the phenomena (Personality and Impostor Phenomenon), as well as a quantitative study, correlating personality, parenting styles and the impostor phenomenon in children. The findings of the review point to the relevance of personality in the levels of impostorism and highlight the gap in the literature on the subject. The empirical study points out that parental perception and personality exert a significant influence on impostor feelings. Keywords: personality traits, imposter phenomenon, parenting styles, children.